Improving Education Management in African Countries - World Bank (Washington, DC, 2013)
The World Bank, jointly with its partners, the governments of France, Ireland and Norway, and later with Education Program Development Fund (EPDF) support with technical support from the Pole de Dakar and Cooperation Francaise/AFD, launched AGEPA as a regional pilot program in five countries in 2003/2004. This completion report provides an overview of the technical assistance activties, outputs and lessons learned; and the financials of the initiative. The following provides the sector context for the initiative. At the current stage of the Education for All (EFA) process, better management and accountability at the local, school and classroom levels play an essential role in raising education quality and reaching universal primary school completion. Since 2002, Sub-Saharan African (SSA) countries have made considerable progress in access to education, with primary completion rates increasing from 49 percent in 2000 to 60 percent in 2006. However, the advances in primary completion are not sufficient to achieve the EFA goals, and education quality remains very weak. Though more than 90 percent of African children enter primary education, only two-thirds of those reach the final grade. Moreover, only 50 percent of students master the basic competencies the system set out to teach them at the end of primary schooling. Building institutional capacity at all levels of the system is also essential for the success of policies such as decentralization, school-based management and school grants that most countries in the region have adopted in recent years. African education policy makers and local education administrators (inspectors, school directors etc.) increasingly emphasize that the implementation of EFA plans at the grassroots level remains a major challenge.